PPV Criterion of a Defect Rock Slope under Blasting SV-Waves - Shiwei Lu; Yingkang Yao; Yongsheng Jia; Jinshan Sun; Zhen Zhang (Shock and Vibration)
In order to estimate the stability of slopes with geological defects during blasting excavations, the dynamic responses of a rock slope with a fault subjected to blasting seismic waves are studied. The SV-component of blasting seismic waves is considered and the fault is simplified as a semi-infinite crack in an unbounded space. In the background of an iron mine in central China, the relation between the stress field and the PPV of the incident wave is analyzed and the function of PPV threshold is deduced using both deterministic and probabilistic methods to evaluate the slope stability. Results show that the PPV threshold increases monotonically with the increasing frequency and reaches the lowest point at around γ1 = 14°, which should be proposed as the PPV threshold. The PPV threshold is with an about 50% failure probability when the mean values of mechanical parameters are taken. On the safe side, a more rigorous PPV threshold with only 5% failure probability is determined as 2.25 cm/s for f ≤ 10 Hz, as 2.25 cm/s-5.02 cm/s for 10 Hz < f ≤ 50 Hz, and as 5.02 cm/s-10.05 cm/s for f > 50 Hz. A through structural surface is likely to occur inside the northern slope once the PPV exceeds the proposed threshold.